The meaning and concept of public safety and order - D. S. Tykhonova (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the analysis of the legal category of public safety and order, because it is currently relevant and researched in our country. This question plays an important and great role in our social life, which is determined by the highest social values of a person and a citizen. Therefore, it is the state that is entrusted with the task of fully ensuring public safety, public order and peace of our society.The article studies the scientific research in this area, considers and analyses many views of state and foreign scientists, pays much attention to the meaning and concept of "public safety" and "public order", defines the purpose and objectives of the scientific research. A comparison of concepts with related notions such as “public safety” and “public order” has been also made. Ukrainian explanatory dictionary has been used for analysis and justification.The article also mentions many scholars, their works and their interpretations, as well as their agreement and disagreement regarding the considerations of public safety and order. The view on the definition of the concepts of public safety and public order in the context of the National Police of Ukraine has been specified. And it has been also stated that the concept of “public safety” and “public order” is absorbed by a broader and more meaningful concept, such as “civil safety” and “civil order”.The opinions regarding the identification of concepts and terms have been substantiated. It has been appealed to the Basic Law of the State, namely the Constitution of Ukraine and to the Law of Ukraine “On the National Police of Ukraine”. The concepts of “public safety” and “public order”, as well as “civil safety” and “civil order” have been studied. The tasks and principles of the National Police of Ukraine have been mentioned. Attention has also been paid to the broad and narrow aspects of the concept of “public order”. At the end of the article, it has been rightly noted that the simultaneous use or identification of these concepts continues the legal conflict in the field of public security and order.